PERTUMBUHAN EKONOMI DAN EMISI KARBON ANALISIS HIPOTESIS ENVIRONMENTAL KUZNETS CURVE (EKC) PADA NEGARA HIGH INCOME DI KAWASAN ASEAN TAHUN 1998-2018 - Azarya hendry christy; Sakti, Rachmad Kresna (Journal of Development Economic and Social Studies, 2022)
The objective of this research is to analyze the relationship between economic growth, which uses per capita Gross Domestic Product (GDP), and environmental degradation, which uses metric/ton carbon emission. This study was conducted in high-income southeast Asian countries incorporating 1998-2018 time-series data. Here investment represented by Foreign Direct Investment, population growth, and industrial growth were also used as the independent variables. The use of panel data regression with the fixed effect model has led to evidence that EKC, based on the inverted-U curve between economic growth and industrial growth positively affects environmental degradation and that population growth and investment negatively influence environmental degradation as explained by the increase in carbon emission.